2017
DOI: 10.1371/journal.pone.0168932
|View full text |Cite
|
Sign up to set email alerts
|

Chest Fat Quantification via CT Based on Standardized Anatomy Space in Adult Lung Transplant Candidates

Abstract: PurposeOverweight and underweight conditions are considered relative contraindications to lung transplantation due to their association with excess mortality. Yet, recent work suggests that body mass index (BMI) does not accurately reflect adipose tissue mass in adults with advanced lung diseases. Alternative and more accurate measures of adiposity are needed. Chest fat estimation by routine computed tomography (CT) imaging may therefore be important for identifying high-risk lung transplant candidates. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…The adipose tissue volume was calculated to assess obesity as a comorbidity and as a crude estimate of patient size (height and weight were not available). Adipose tissue volume and was estimated by density interval between -170HU and -40HU on a single slice at level of T7-T8 [16].…”
Section: Ct Images Analysismentioning
confidence: 99%
“…The adipose tissue volume was calculated to assess obesity as a comorbidity and as a crude estimate of patient size (height and weight were not available). Adipose tissue volume and was estimated by density interval between -170HU and -40HU on a single slice at level of T7-T8 [16].…”
Section: Ct Images Analysismentioning
confidence: 99%
“…Fourth, the measurement of single slice cross-sectional area of adipose may not entirely reflect the total adiposity. Prior work has demonstrated a significant correlation between single slice cross-sectional area and total volume of adipose 37,38 ; additionally, our measures of adipose were highly correlated with traditional measures of body composition suggesting that we are measuring the tissue of interest. Fifth, the divergent findings in abdominal and thoracic subcutaneous adipose could also reflect either (1) different populations rather than the differential effects of the 2 distinct anatomical adipose depots or (2) differences in adipose measurement related to the use of clinically indicated rather than protocolized research thoracic CT scans.…”
Section: Discussionmentioning
confidence: 57%
“…Using a standardized anatomical space approach, 37,38 our group previously identified that the maximum correlation between the total volume of thoracic SAT and single slice area of thoracic SAT is found at the mid-T8 vertebral level (Pearson's r = 0.97), and maximum correlation between the total volume of thoracic VAT and single slice area of thoracic VAT is found at the mid-T7 vertebral level (Pearson's r = 0.86). 37 Using this technique, we identified the single slice cross-sectional area of thoracic VAT and thoracic SAT ( Figure 1C-D). There was high interrater reliability with an intraclass correlation coefficient of 0.98 for the thoracic SAT and 0.97 for the thoracic VAT (Supplementary Figure S1A-B).…”
Section: Measurement Of Chest Ct Adipose Tissue Areamentioning
confidence: 99%
“…For example, without a precise definition of the boundaries of the thoracic body region and intrathoracic adipose tissue region, standardized quantification of intrathoracic fat becomes impossible. [1][2][3] Standardized object definitions can also facilitate enriching and sharpening prior knowledge that is encoded into and utilized in methods for localizing objects body-wide 4,5 and distinguishing different patient groups. 6,7 In this spirit, body region definition becomes just as important as or even more important than objects contained in the body region.…”
Section: A Backgroundmentioning
confidence: 99%
“…For developing generalizable methods that operate body‐wide, for meaningful use of quantitative information, and for standardized clinical operation, standardized definitions of these objects become essential. For example, without a precise definition of the boundaries of the thoracic body region and intrathoracic adipose tissue region, standardized quantification of intrathoracic fat becomes impossible . Standardized object definitions can also facilitate enriching and sharpening prior knowledge that is encoded into and utilized in methods for localizing objects body‐wide and distinguishing different patient groups .…”
Section: Introductionmentioning
confidence: 99%